Scribes' Voices: The Relevance and Types of Early Medieval Colophons - Schiegg, Markus (Studia Neophilologica, 2016)
Early medieval colophons are the scribes' inscriptions at the end of a manuscript, in which they provide some kind of information about their copying endeavour. After focusing on the colophons' relevance for manuscript studies and, among other fields, for cultural history and linguistics, this paper illustrates how existing research has either collected them as antiquarian curiosities' (Moreno Olalla 2013: 144) or has traced the development of single formulae and used them to reconstruct the diachronic, diatopic and diastratic distribution of colophons and manuscripts. Based on different kinds of colophons, this contribution establishes a classification of colophons with regard to formal, contextual and functional characteristics. Linguistic Speech Act Theory is applied to classify the huge variety of colophons according to four basic categories of human communication. Finally, the article discusses how colophons changed when the early medieval, monastic scriptoria were replaced by late medieval, secular book shops.
Keywords: colophons; manuscripts; scribes; medieval studies; Speech Act Theory